Productivity, economics and soil fertility under different maize (Zea mays) varieties as influenced by soil ameliorating practices in North Eastern hill region of India - G I, RAMKRUSHNA; DAS, ANUP; LAYEK, JAYANTA; BABU, SUBHASH; VERMA, B C; PATEL, D P; KRISHNAPPA, R; SAVITA, SAVITA; NGACHAN, S V (The Indian Journal of Agricultural Sciences, 2018)
A field experiment was conducted during kharif seasons of 2011 and 2012 at ICAR Research Complex for NEH Region, Umiam (966 m above mean sea level), Meghalaya, to identify suitable maize varieties and nutrients management practices for higher maize productivity. Results revealed that, application of recommended dose of fertilizer (RDF, 80:26.2:33.2 kg NPK/ha) along with furrow application of lime @ 250 kg/ha + FYM @ 5 t/ha produced the highest grain yield (4.70 and 4.87 tonnes/ha in 2011 and 12, respectively) followed by RDF + furrow application of lime @ 500 kg/ha. Grain yield obtained under RDF + lime@ 250 kg/ha + FYM@ 5 t/ha was 38.0 and 31.3% higher than that of RDF alone for the year 2011 and 2012, respectively. There was no significant effect of arieties on grain yield of maize although RCM 1-3 recorded relatively higher grain yield followed by RCM 75. The ameliorating practices significantly improved the soil chemical properties such as soil pH, soil available N and P, soil organic carbon and significantly reduced exchangeable Al and exchangeable acidity. The variety RCM 1-3 with RDF+ furrow application of lime (250 kg/ha) + FYM (5 tonnes/ha) was found superior as compared to other treatments.